2018
DOI: 10.14687/jhs.v15i2.5208
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of summarization skills of primary school students<p>İlkokul öğrencilerinin özetleme becerilerinin incelenmesi

Abstract: In order to understand a text or a book better and enhance the comprehension skills, a great number of strategies and methods is used in the process of reading. One of these is summarizing strategy that is employed after reading. Summarizing is the creation of a text corresponding to the original text on a small scale as its shorter form, by keeping the main theme and content of a text and through excluding less important information and details.The objective of this research made is to analyze the primary sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In some studies in the literature, it has been found that students do not write abstracts at regular intervals (Bulut, 2013;Kuşdemir et al, 2018). A similar conclusion was reached in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In some studies in the literature, it has been found that students do not write abstracts at regular intervals (Bulut, 2013;Kuşdemir et al, 2018). A similar conclusion was reached in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The quality of the written summaries is an important clue for the determination of the level of reading comprehension. Kuşdemir, Düşünsel and Çelik (2018) found that the elementary school fourth grade students' summary writing scores vary significantly depending on the gender of the classroom teacher. The students whose classroom teacher is male were found to be more successful in writing summary.…”
Section: Resultsmentioning
confidence: 95%
“…Studies in the literature indicate that the number and quality of activities aimed at summarizing in the teaching tools used in the education process are insufficient. Teachers do not give enough activities related to summarization strategies, and the summarization skills of middle school students are weak (Karadağ, 2019;Kuşdemir & Düşünsel, 2018;Ülper & Arıca Akkök, 2010;Ülper & Yazıcı Okuyan, 2010). This situation hinders the development of skills and strategies related to summarization in L1 in the early period.…”
Section: Discussionmentioning
confidence: 99%